Retracted: Firm Adaptation, Preadaptation, and Sequential Ambidexterity in Firm Boundaries During an Era of Ferment and an Era of Incremental Change. Issue 3 (31st July 2017) - Patel, Chirag; Husairi, Mariyani Ahmad
Abstract : The above article, published online on 31 July 2017, in Wiley Online Library (wileyonlinelibrary.com ), has been retracted by the journal's Editor‐in‐Chief, Gloria Barczak, the Product Development and Management Association, and Wiley Periodicals, Inc. The retraction has been agreed due to the unattributed overlap with a previously published article, authored by the corresponding author (Patel, C. and Haon, C. (2014), The Complementary Role of Branding. European Management Review, 11: 173‐186.https://doi.org/10.1111/emre.12029 ), and inconsistencies in construct names within the article.